Municipal solid waste or MSW has potency to be decomposed by microorganisms and trasformed into compost. The waste contains 60%-75% of organic materials C, H, O, and N. The aim of this research was to develop a simulation model based on mathematical equations describing the phenomenon of the composting. The population of microorganisms , the rate of O2 consumption , the rate of CO2 production , the rate of H2O production, the rate of carbon nitrogen ratio or C/N, and temperature were the v - Yohanes Setiyo; Hadi K. Purwadaria; Arief Sabdo Yuwono; M. Ahkam Subroto (Forum Pasca Sarjana, 2007)
Municipal solid waste or MSW has potency to be decomposed by microorganisms and trasformed into compost. The waste contains 60%-75% of organic materials C, H, O, and N. The aim of this research was to develop a simulation model based on mathematical equations describing the phenomenon of the composting. The population of microorganisms , the rate of O2 consumption , the rate of CO2 production , the rate of H2O production, the rate of carbon nitrogen ratio or C/N, and temperature were the variables tested in this research. Validation was carried out by comparing datum of simulation model with datum of composting. Simulation model was declared valid if the values of each parameter were r2 > 0.75, the total value of Err was closed to zero, and the distribution of Err was independent to time. The sensitivity test was analyzed by comparing the value changes of variable tied with the value changes of free variable. Correction from the simulation model in predicting the microorganism population, CO2, O2, and temperature could be expressed respectively as y’ = 1.06(y-1.003), y’ = 1.07(y+ 0.07), y’ = 1.02(y+ 0.05), and y’ = 1.02(y - 1.05). The temperature, the C/N and the rate of O2 consumption were sensitive to the changes of microorganism population and the radius of the bioreactor. Key words: composting, organic materials, simulation, bioreactor